2019
DOI: 10.1017/s1742170519000310
|View full text |Cite
|
Sign up to set email alerts
|

Farmer perspectives and experiences introducing the novel perennial grain Kernza intermediate wheatgrass in the US Midwest

Abstract: Kernza® intermediate wheatgrass (Thinopyrum intermedium) is a novel perennial grain and forage crop with the potential to provide multiple ecosystem services, which recently became commercially available to farmers in the USA. The viability and further expansion of this promising crop require understanding how it may fit the needs of farmers’ livelihoods and the structure of their farming systems. However, no prior research has studied the perceptions and experiences of Kernza growers. The goals of this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 31 publications
3
63
0
Order By: Relevance
“…In our study the level of nitrogen fertilization did not have an impact on weed productivity, and this may suggest that IWG has a belowground competitive advantage for nutrient resources. Our findings are consistent with the observation by several farmers who noted enhanced weed suppression over time in IWG cropping systems compared to annual cereal cropping systems (Lanker et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study the level of nitrogen fertilization did not have an impact on weed productivity, and this may suggest that IWG has a belowground competitive advantage for nutrient resources. Our findings are consistent with the observation by several farmers who noted enhanced weed suppression over time in IWG cropping systems compared to annual cereal cropping systems (Lanker et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…For instance, in another research site at Lancaster, WI, with a land history of pasture and perennial forages, we observed that IWG plots managed for dual use under grazing became invaded by Canada thistle and perennial grasses (data not shown). Farmers who are currently growing IWG observed major changes in weed community composition from annual weed species to predominantly perennial weed species (Lanker et al., 2019). The most commonly observed weed species in IWG cropping systems were Canada thistle, red clover ( Trifolium pratense L.), yellow sweetclover, Kentucky bluegrass ( Poa pratensis L.), and other perennial species, as well as the annual species waterhemp [ Amaranthus tuberculatus (Moq.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations